Two- to five-year follow-up of 78 patients after treatment with the Flow Redirection Endoluminal Device. Issue 1 (February 2020) - Luecking, Hannes; Doerfler, Arnd; Goelitz, Philipp; Hoelter, Philip; Engelhorn, Tobias; Lang, Stefan
Background and purpose: Flow-diverter stents are well-established for the treatment of cerebral aneurysms. Flow Redirection Endoluminal Device differs from other flow-diverter stents by its dual-layer design and has proved equality to other devices in numerous short-term surveys. However, follow-up data covering substantially more than one year are still limited for this device. We present our long-term experience with Flow Redirection Endoluminal Device. Materials and methods: Seventy-eight patients harboring distal internal carotid artery (91%) or vertebrobasilar (9%) cerebral aneurysms treated with Flow Redirection Endoluminal Device with or without adjunctive coiling met the inclusion criteria. All cases were evaluated for aneurysm occlusion (according to Modified Raymond Roy Classification, MRRC), for flow-diverter stents patency and configuration and for procedure- and device-related morbidity and mortality. Results: Mean follow-up interval was 36.9 ± 9.5 months (<30 months: n = 18; 31–42 months: n = 31; >42 months: n = 24). Total and subtotal aneurysm occlusion after six months was assessed in 92.0% (MRRC1  = 77.3%, MRRC2  = 14.7%, MRRC3a  =2.7%, MRRC3b  = 4.1%) and increased to 95.9% (MRRC1  = 90.5%, MRRC2  = 5.4%, MRRC3a  = 2.7%). There was one case of aneurysm growth requiring early re-treatment. Procedure-related morbidity was observed in three cases (3.8%; one transient hemiparesis, one suspected foreign-body reaction, and one micro-wire perforation). There was no procedure- or device-related mortality. In-stent stenosis due to intimal hyperplasia was observed in two cases and fish-mouthing in three cases. Conclusions: Our long-term data covering two to five years after flow diversion confirm that Flow Redirection Endoluminal Device is a safe and effective device for the treatment of cerebral aneurysms with progressive high aneurysm occlusion rates; recurrence rates were very low. Overall device-related morbidity was low and was not observed later than six months after intervention.